Teen-age secret agent stories - Furman, A. L. (Abraham Loew), 1902-; Woolgar, Jack E (Inc., New York : Lantern Press, 1970)
Five short stories in which young people find themselves helping government espionage agents get their man.
Keywords: Short stories